Centennials Information Ecosystem: A Portrait of Gen Z as Potential Information Consumers of Mainstream Media - Permatasari, Andalusia Neneng; Kusumalestari, Ratri Rizki; Satriani, Arbaiyah; Afyadi, Yuki Jauza Hasna; Saraswati, Sarry Shafina (JURNAL KOMUNIKASI INDONESIA, 2024)
Generation Z, also known as the centennials, has been widely discussed in various studies. Gen Z's behavior in consuming news and information is shown in the way they access information, choose news topics and media platforms, and determine which media they will frequently go to specifically. The purpose of this study is to explore Gen Z's consumption of news on mainstream media and the factors that influence it, and to delve into their perceptions of the function of mainstream media in exercising social control and being a trusted source of information. The method used in the research is qualitative with a case study approach. The results show that Gen Z's exploration of information is influenced by interest, locality, proximity, self-satisfaction, and incidental matters. These five factors are closely related to the specific characteristics of Gen Z and can be input for local and national mainstream media to follow the direction of development that is now held by the young generation. Mainstream media also remains Gen Z's reference for truth verification; even though they do not have a tendency to be loyal to one media and deliberately access the web pages of mainstream media directly.